CONSTITUTIONAL AND LEGAL DEVELOPMENT OF THE REPUBLIC OF THE PHILIPPINES AND PECULIARITGIES OF THE 1987 CONSTITUTION - A. N. Pankov (Vestnik MGIMO-Universiteta)
The article analyzes the stages of constitutional development of the Philippines, the principles and characteristics of the various constitutional acts adopted in the American colonial period and after the country's legal independence. Particular attention is paid to the principles and the specific characteristics of the current constitution of 1987, as well as the constitution of 1935, which was the first basic law, which laid the foundations of western constitutional model and the basic principles characteristic of the constitutions of democratic countries, including progressive for that time legal status of the individual, based on the "Bill of Rights" and directly borrowed from the American constitutional system. The question of the national state of one of the countries in South-East Asia is also analyzed which is of considerable scientific interest in terms of the perception of the Western model of democracy and attempts at planting on alien for these models of socio-economic and political framework. The author mentions how, after the provision of legal independence from the U.S. in 1946, the Philippines went the way of the serious distortion of the principles of "Western democracy". There was a wide gap between the formal democratic constitutional institutions of the Western model and the actual breaking of on the basis of eastern states with traditionally immature social structure, backward productive forces. The author shows that the U.S. attempts to impose its former colony model of American state and legal institutions that would facilitate the establishment of the South- East Asia "window of Western democracy", and could serve as a role model for the layout of other countries, not only in South-East Asia but also in Africa and Latin America, suffered a fiasco.